Kalinangan 1996 [held at] Osaka University of Foreign Studies, Department of Philippine Studies on November 4, 1996 (s.n., 1996)
Cultural presentation of students at the Department of Philippine Studies Department in Osaka, featuring Philippine dances and songs and a skit about the Philippine flag.